Obstetric and neonatal outcome of COVID-19 positive mothers: A retrospective cohort study in a tertiary care hospital of West Bengal - Sujoy Biswas,; Mallika Sengupta,; Mandira Roy,; Rajesh De, (Asian Journal of Medical Sciences, 2023)
Background: Coronavirus disease was declared a global pandemic by WHO in March 2020 and since then several reports on obstetric and neonatal outcomes due to COVID-19 infection in pregnancy are showing varying results from different corners of the world. Aims and Objectives: The aim of the present study was to describe the clinical course of the disease in pregnancy and evaluation of maternal and neonatal outcomes. The secondary objective was to compare the obstetric and neonatal outcomes of COVID-19-positive mothers and COVID-19-negative mothers admitted in the same time frame. Materials and Methods: In this retrospective cohort study we included 155 COVID-positive and 310 COVID-negative pregnant women, from May 2020 to December 2020 admitted at our tertiary care hospital in West Bengal, India. Maternal and neonatal outcomes were compared in both groups. Results: Most of the COVID-positive pregnant women were asymptomatic (38%), 45.8% of patients had mild symptoms like fever and cough and only 1.9% of mothers developed severe pneumonia. Pregnancy complications like abortion, stillbirth, intrauterine fetal death, antepartum haemorrhage, pregnancy-induced hypertension, gestational diabetes mellitus were similar in both groups (P>0.05) but significantly increased incidence of preterm labor and delivery of the low-birth-weight baby was found in the COVID-positive group (P<0.05). Number of neonates with low birth weight (<2.5 kg) was significantly higher in the COVID-positive group than in COVID negative group (28% vs. 16.7%, P<0.05). Need for neonatal intensive care unit admission was similar in both groups (P>0.05). Conclusion: Significantly increased incidence of preterm labor and delivery of the low-birth-weight baby was found in the COVID positive mothers without any evidence of mother-to-child vertical transmission of SARS-CoV-2.